The Ploy of Instinct : Victorian Sciences of Nature and Sexuality in Liberal Governance - Frederickson, Kathleen (Book collections on Project MUSE., 2014)
It is paradoxical that instinct became a central term for late Victorian sexual sciences as they were elaborated in the medicalized spaces of confession and introspection, given that instinct had long been defined in its opposition to self-conscious thought. The Ploy of Instinct ties this paradox to instinct's deployment in conceptualizing governmentality. Instinct's domain, Frederickson argues, extended well beyond the women, workers, and ""savages"" to whom it was so often ascribed. The concept of instinct helped to gloss over contradictions in British liberal ideology made palpable as turn-